The Research on the Legal Process about Freedom Right of the Press in United States - Wang, Shiyun (Advances in Social Sciences Research Journal, 2016)
Throughout the development history of communication, the state power always takes a variety of methods to impede the free spread of information, so as to vindicate their rule and authority. Promulgating laws is the most effective and most used method to ban the right of publish freedom and the right of inform. Face to so rigorous restriction of state power, the public made long term and hard fight for free spread of information. The paper focus on the regulations which concerned about journalism in colonial period and democratic period of American and want to interpret the struggle public made in order to strive for the free spread of information. Under the pressure public made, the government has to change policies and laws and guarantee the freedom right to public. But at the same time, the power factor still strong enough to influence the free spread of information and still is able to control the press if it want. There is a long way to go to the freedom world.